#TITLE_ALTERNATIVE# - GUNAWAN (NIM 10104079), GANJAR
In its transportation through the pipeline, there is possibility that the gas would condense when pressure and temperature of gas change. The gas temperature change is caused by temperature difference between flowing gas and its surrounding. Gas pressure change is caused by friction, pipe inclination, and gas acceleration. In compositional model, the change of phase composition which is caused by the change of gas temperature and pressure is taken into account for calculating the pressure drop. The equation of pressure drop using Beggs-Brill correlation is influenced by pipe lenght, vapor mole fraction, compressibility factors, equilibrium ratio each component, and gas temperature. Those factors are given implicitly from flash equation, Soave-Redlich-Kwong ( SRK) Equation of State (EOS), equation of fugacity of liquid and vapor phase each component, and temperature equation. Here, the pressure drop is solved numerically by the 4th order Runge-Kutta method in which genetic alghorithm is being used for solving the implicit relations.